Market Reaction to the Announcement of Rights Issues in Bank Sub-Sector Issuers on the Indonesian Stock Exchange - Noor Hafia Rezki; Yusniar, Meina Wulansari (HM Publisher, 2024)
The TVA metric is used to evaluate the liquidity of a particular stock. Utilizing a technological tool called trading volume activity (TVA) can help monitor capital markets' response to information. The inverse relationship between TVA value and stock liquidity causes this. The TVA value of a stock increases with how easy it is to sell and convert it into currency, or more precisely, how much liquidity a stock has. Because of the announcement right issue, certain phenomena have good impact phenomena, while other phenomena turn out to have bad impacts, and because TVA was not covered in previous research, it is known that the effect of notification light issue on stock returns and market trading volume do not always have the same effect on offering the same conclusions. The research sample consisted of 17 financial services companies in the banking sub-sector that dealt with this issue. The window period in this research was carried out for 11 days, namely 5 days before the announcement right issue, 1 day at the time of the announcement, and 5 days after the announcement right issue. The data used is secondary data obtained from the Indonesian Stock Exchange page and yahoo finance. Data collection techniques are carried out using methods of purposive sampling. Data analysis techniques using one sample t test to find out the market reaction around the announcement right issue and comparative tests to determine differences abnormal return and trading volume activity before and after the announcement right issue. The research results show that there is abnormal return significant surrounding the announcement event rights issue Bank subsector issuers on the IDX in 2021. There is no difference between abnormal returns significantly before and after the announcement of the rights issue. There is a significant difference in stock liquidity before and after the announcement rights issue which is indicated by different trading volume activities.